1348 Quality Improvement Project to Promote Betablocker Therapy Post CABG In Patients with Low Left Ventricular Ejection Fraction (LVEF): A Single Centre Study. (12th October 2021) - Roy, Dorina; Aljanadi, Firas; Jones, Mark
Abstract: Aim: Statistically significant and strong evidence suggests that beta-blockers reduce the number of deaths in patients with reduced LVEF (<35%). The 2017 European Association for Cardio-Thoracic Surgery (EACTS) guidelines for perioperative medications in cardiac surgery recommended betablockers should be commenced or continued on discharge for patients with low LVEF after Coronary Artery Bypass Graft (CABG). The EACTS recommends the use of Bisoprolol, Metoprolol, Carvedilol and Nebivolol. We aimed to assess the discharge prescription of patients undergoing CABG at a regional tertiary care centre. Method: A retrospective observational analysis of patients admitted between 2013 and 2020 with low LVEF was done. A. total of 101 patients were finally included. Electronic care records of patients were reviewed to collect patient data, including clinic and discharge letters. Audit registration was conducted as per local hospital policies. Results: Demographics revealed average age to be 66 years. There were 23% females and 77% males. Out of 101 patients, 90 (89%) patients were discharged with betablockers. 11 (11%) patients were not discharged with Betablockers. 83 (81%) patients were discharged with recommended betablockers. Conclusions: This comprises the first cycle of the audit. Data is currently being analysed for a second cycle. Findings from this audit suggest good compliance with established guidelines, however there is scope for improvement. We employed simple measures like departmental presentation and raising awareness. Additional methods such as inclusion in discharge checklists is also a recommendation. Outcome from the second cycle will guide further interventions and data from both cycles will be presented at the meeting.